2012
DOI: 10.33301/2012.14.03.04
|View full text |Cite
|
Sign up to set email alerts
|

Income and Life Quality of Farmer Households Suffering Social Exclusion

Abstract: This study uses descriptive statistical method to analyze the income and life qual- ity of 397 farmer households who are suffering social exclusion in an economic aspect out of a total of 725 households surveyed in five Northern provinces of Vietnam in 2010. The farmers’ opinions of the impact of the policies currently prac- ticed by the central government and local authorities to give them access to the labor market are also analyzed in this study to help management officers see how the poli- cies affect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In developed countries, the situation is better than in developing countries, where farmers face poor welfare regimes, limited access to market, and pricing strategy. At the same time, labor practices, class privilege, farmers' education, income gap, and leadership skills influence social capital, which eventually has a direct effect on social exclusion (Dribe & Svensson, 2008;Ngoc Anh et al, 2012;Black et al, 2019). Goal 5 in SDGs is gender equality, as women's inequality in agriculture is also the reason for female farmers' social exclusion (Centrone et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In developed countries, the situation is better than in developing countries, where farmers face poor welfare regimes, limited access to market, and pricing strategy. At the same time, labor practices, class privilege, farmers' education, income gap, and leadership skills influence social capital, which eventually has a direct effect on social exclusion (Dribe & Svensson, 2008;Ngoc Anh et al, 2012;Black et al, 2019). Goal 5 in SDGs is gender equality, as women's inequality in agriculture is also the reason for female farmers' social exclusion (Centrone et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Developed economies have a good structure to support their farmers, whereas developing economies, due to their weak fiscal systems, often tax them. Ngoc Anh et al (2012) examine the life quality and income of farmers suffering from the issue of social exclusion and high poverty. The study found that 397 out of 725 farmer's households are socially excluded economically from the rest of society in the Northern area of Vietnam.…”
Section: Government Intervention and Social Mobilitymentioning
confidence: 99%
“…These quintiles include poor, near-poor, middle, above average, and rich. According to the classification of the social exclusion in the economic aspect of the people proposed by Mai et al (2012), the number of identified informal workers in Northern mountainous areas under the influence of social exclusion in economic aspect identified was 358 people, from which 59 were in the third quintile -the group with middle income (Table 1). Questionnaires were designed based on a continuous and ordinal scale (Likert scale) to collect independent variables' data.…”
Section: Methodsmentioning
confidence: 99%
“…These activities are indicators for tackling social exclusion in an economic aspect, as mentioned by Burchardt et al, (1999). According to Mai et al, (2012), the economically excluded people include those with income above the Quintile 3 but lower than the Quintile 4, by 60%; poor and near-poor people belong to this category. In general, having a job means that workers have a higher income than those receiving subsidies from the State, community, and society.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation